El problema de la traducción de la Biblia al español en el siglo XVI y su resonancia en algunos catecismos dominicos para la misión en el Nuevo Mundo = The Problem of Translating the Bible into Spanish in the Sixteenth Century and its Resonance in some Dominican Catechisms for the Mission in the New World - Delgado, Mariano 1955- (2025)
The use of the Bible in 16th-century Dominican catechisms for the mission in the New World has been little studied until now and requires broader contextualisation. The paper begins with the general problem of translating the Bible into Romance languages in the Hispanic world of the 16th century. It continues with the controversy on the issue within the Order of Preachers between Bartolomé Carranza and Melchor Cano after the spiritual shift that took place in the 1550s. It then presents the use of the Bible in some 16th-century Dominican catechetical works for the mission in the New World. Finally, before drawing some conclusions, it analyses how the Dominican Bartolomé de Las Casas quotes the Bible, especially in his great "Letter to the Council of the Indies" of 20 January 1531, written in Spanish.
Keywords: Bartolomé Carranza; Bartolomé de Las Casas; Juan de Zumárraga; Melchor Cano; catecismos dominicos del siglo XVI para el Nuevo Mundo; traducción de la Biblia al español